Understanding physicians' professional knowledge and practice in research on skilled migration. Issue 4 (3rd July 2016) - Weiß, Anja
ABSTRACT: Research on the integration of migrant professionals into high-skilled labor markets either focuses on differences between nation states which may be exacerbated by national closure or it celebrates the global versatility of professional knowledge, especially in the natural and health sciences. Building on a pragmatist approach to professional knowledge, the article argues that professional knowledge should not be seen as either universal or local, but both the institutionalized and the incorporated aspects of cultural capital are characterized by 'local universality'. Professionals recreate professional knowledge in specific 'local' situations by relating to universal standards and to internalized 'libraries' of situated expert experience. While the more common notion of knowledge as a socially contested resource continues to be relevant for research on skilled migration, professional knowledge should also be seen as emerging in situations in response to socio-material problems. These problems can be structured by the nation-state, but they can also be transnational in nature.